Manajemen strategi bank syariah dalam mengembangkan digital marketing yang berlandaskan prinsip syariah - Hidayah, Anadia Hidayah (Maliki Interdisciplinary Journal, 2025)
The development of digital technology provides significant opportunities for financial institutions, including Islamic banks, to expand their service reach and improve marketing efficiency. Digital marketing is a key strategy for attracting new customers and maintaining the loyalty of existing ones. However, the implementation of digital marketing in Islamic banks must remain based on Islamic principles, such as honesty, transparency, fairness, and avoidance of gharar (uncertainty) and maysir (speculation). This study used qualitative data collection methods through literature review and analysis of several relevant journals. The results of the discussion indicate that effective digital marketing implementation in Islamic banks requires strong digital literacy, Islamic-based product innovation, and oversight of compliance with Islamic principles. Therefore, a management strategy based on Islamic values ​​can create competitive advantage while maintaining the integrity of Islamic financial institutions in the digital era.